2019
DOI: 10.1016/j.ijcha.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of clopidogrel only vs. clopidogrel added proton pump inhibitors in the treatment of patients with coronary heart disease after percutaneous coronary intervention

Abstract: Background Controversy still exists that whether clopidogrel should add proton pump inhibitors (PPIs) in patients with coronary heart disease after percutaneous coronary intervention (PCI). The aim of this study was to evaluate the efficacy and safety of clopidogrel added proton pump inhibitors (PPIs) vs. clopidogrel for the treatment of patients with coronary heart disease after percutaneous coronary intervention (PCI). Methods and results We systematically searched Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…Clopidogrel is associated with increasing risks of gastrointestinal (GI) bleeding both when given alone or in combination with aspirin [ 4 , 20 ]. Consequently, clopidogrel is commonly prescribed in combinations with PPIs to prevent GI bleeding [ 4 , 7 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clopidogrel is associated with increasing risks of gastrointestinal (GI) bleeding both when given alone or in combination with aspirin [ 4 , 20 ]. Consequently, clopidogrel is commonly prescribed in combinations with PPIs to prevent GI bleeding [ 4 , 7 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clopidogrel is associated with increasing risks of gastrointestinal (GI) bleeding both when given alone or in combination with aspirin [ 4 , 20 ]. Consequently, clopidogrel is commonly prescribed in combinations with PPIs to prevent GI bleeding [ 4 , 7 , 20 , 21 ]. According to Flockhart and others, the PPIs are inhibitors of CYP2C19 with esomeprazole reported as a strong inhibitor and pantoprazole, lansoprazole and omeprazole as weaker inhibitors [ 12 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omeprazole and other PPIs have come under increased scrutiny because they are pervasively prescribed and used, frequently at doses that are higher than required to inhibit acid secretion and for longer periods than are clinically indicated [ 10 13 ]. Furthermore, a series of investigations has linked PPI use to a number of conditions that include cardiovascular disease [ 14 ], osteoporosis [ 15 ], C. Difficile colitis [ 16 ], community acquired pneumonia [ 17 ], and dementia [ 18 20 ], though different groups have arrived at opposite conclusions [ 21 , 22 ]. The causal effect on these conditions has been debated, though a recent randomized control study suggested that only enteral infections were increased by pantoprazole administration within a three year follow-up period [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 In this case, lansoprazole and pantoprazole could be considered as a rational choice. 34 In terms of cost-effective prescribing, the DDC results showed that the highest average daily costs of PPIs were injectable omeprazole, followed by oral esomeprazole. Thus, the result indicated that these patients paid a higher price when these drugs were prescribed.…”
Section: Open Accessmentioning
confidence: 99%